Magazine

A new formulae method for solving the simultaneous equations

Description
INTERNATIONAL JOURNAL OF SCIENTIFIC & TECHNOLOGY RESEARCH VOLUME 6, ISSUE 03, MARCH 2017ISSN 2277-8616A New Formulae Method For Solving The Simultaneous…
Categories
Published
of 5
All materials on our website are shared by users. If you have any questions about copyright issues, please report us to resolve them. We are always happy to assist you.
Related Documents
Share
Transcript
INTERNATIONAL JOURNAL OF SCIENTIFIC & TECHNOLOGY RESEARCH VOLUME 6, ISSUE 03, MARCH 2017ISSN 2277-8616A New Formulae Method For Solving The Simultaneous Equations Avinash A. Musale, Eknath S. Ugale ABSTRACT: Actually there are too many Methods which are used for solving the various types of equations by various methods. The equations may be like linear, quadratic, simultaneous, radial, and exponential as well as the equations with the number of variables. And for the Simultaneous Equation the methods are like Addition, Substitution, Elimination as well as Graphical Method also. We know there are too many methods like Gauss Elimination, Gauss Seidal, and Jacobi used for solving the Simultaneous Equations. But here we are going to introduce a new Method for solving the Simultaneous Equations as well as the comparison between the Methods above told and the new one. The paper will show you a new easy method for solving the Simultaneous Equation and the difference between the methods that are being used in the colleges which are Gauss Elimination, Gauss Seidal etc. Keywords: Simultaneous, Equations, Formulae, Method, Gauss, Elimination, Derivation ————————————————————1. INTRODUCTION: The paper represents a method for solving the simultaneous equations in a different way. We use the substitution, addition, matrices Methods for solving the simultaneous equations but in this paper the method is related to directly the formulas for solving the simultaneous equations.2. METHOD (FORMULAE): For Two Unknowns – X & Y a11X+a12Y=b1; a21X+a22Y=b2; Solution: u= [(a11*b2 - a21*b1)] v= [(a11*a22 - a12*a21)] Y= X= For Three Unknowns – X, Y & Z a11X+a12Y+a13Z=b1; a21X+a22Y+a23Z=b2; a31X+a32Y+a33Z=b3; Solution: r= [(a11*b3) - (a31*b1)]; s= [(a11*b2) - (a21*b1)]; t= [(a11.a22) - (a12*a21)]; u= [(a11*a33) - (a13*a31)]; v= [(a11*a23) - (a13*a21)]; w=[(a11*a32) - (a12*a31)];+Z=* Y=*+ +X=*For Four Unknowns – X, Y, Z & W a11X+a12Y+a13Z+a14W=b1; a21X+a22Y+a23Z+a24W=b2; a31X+a32Y+a33Z+a34W=b3; a41X+a42Y+a43Z+a44W=b4; Solution: k=[(a11*b4) - (a41*b1)]; l= [(a11*b3) - (a31*b1)]; m= [(a11*b2) - (a21*b1)]; n= [(a11.a22) - (a12*a21)]; o= [(a11*a33) - (a13*a31)]; p=[(a11*a44) - (a14*a41)]; q= [(a11*a23) - (a13*a21)]; r=[(a11*a24) - (a21*a14)]; s=[(a11*a32) - (a12*a31)]; t=[(a11*a34) - (a31*a14)]; u=[(a11*a42) - (a41*a12)]; v=[(a11*a43) - (a41*a13)]; g=(on-sq) h=(vn-uq) i=(ln-sm) j=(tn-sr) e=(kn-um) f=(pn-ur) +W=* Z=*  Avinash A. Musale is currently pursuing bachelor degree in Mechanical Engineering in MIT AOE Pune in Savitribai Phule Pune University, India, Mobile No. +918484972706. E-mail: musaleavinash24@gmail.com  Mr. Eknath S. Ugale is an Assistant Professor in the Department of Mechanical Engineering in MIT AOE Pune, India, E-mail: esugale@mech.mitaoe.ac.inY=* X=*+ + +77 IJSTR©2017 www.ijstr.orgINTERNATIONAL JOURNAL OF SCIENTIFIC & TECHNOLOGY RESEARCH VOLUME 6, ISSUE 03, MARCH 20173. DERIVATION:ISSN 2277-8616or from equation (b) We getFor Two Unknowns – X & Y+X=*a11X+a12Y=b1; a21X+a22Y=b2;orX=*+If u=[(a11*b2 - a21*b1)] v=[(a11*a22 - a12*a21)]Using Gauss Elimination Method Convert the given equations in matrix AX=B form đ?‘Ž11 đ?‘Ž12 đ?‘‹ đ?‘?1 * +** +=* + đ?‘Ž21 đ?‘Ž22 đ?‘Œ đ?‘?2Y=Make the Matrix A as Upper Triangular Matrix X=Make row 1 as following Instruction R1 = R1/a11 đ?‘Ž12′+ * *đ?‘‹+ = *đ?‘?1′+ * 1 đ?‘Œ đ?‘Ž21 đ?‘Ž22 đ?‘?2 a12’=a12/a11 b1’=b1/a11For Three Unknowns – X, Y & Z a11X+a12Y+a13Z=b1; a21X+a22Y+a23Z=b2; a31X+a32Y+a33Z=b3;‌‌‌‌‌.(1) ‌‌‌‌.....(2)By Gauss Elimination Method Convert the given equations in matrix AX=B formMake row 2 as following Instruction R2 = R2 - a21*R1 đ?‘‹ *1 đ?‘Ž12′+ * * + = *đ?‘?1′+ đ?‘Œ 0 đ?‘Ž22′ đ?‘?2′ a22’=a22 - a21*a12’ b2’=b2 – a21*b1’đ?‘Ž11 [đ?‘Ž21 đ?‘Ž31‌‌‌‌ (3) ‌‌‌‌‌‌(4)Make the Matrix A as Upper Triangular Matrix therefore Make row 1 as following Instruction R1 = R1/a11 đ?‘‹ 1 đ?‘Ž12′ đ?‘Ž13′ đ?‘?1′ [đ?‘Ž21 đ?‘Ž22 đ?‘Ž23 ] * [đ?‘Œ ] = [ đ?‘?2 ] đ?‘? đ?‘Ž31 đ?‘Ž32 đ?‘Ž33 đ?‘?3Make row 2 as following Instruction R2 = R2/a22’ đ?‘‹ *1 đ?‘Ž12′+ * * + = * đ?‘?1′ + đ?‘Œ 0 1 đ?‘?2′′ b2’’=b2’/a22’‌‌‌‌‌‌‌(5)We Get‌. đ?‘‹ *1 đ?‘Ž12′+ * * + = * đ?‘?1′ + đ?‘Œ 0 1 đ?‘?2′′Y=**+ +*+a22’= a22 - a21*a12’ a23’= a23 - a21*a13’ b2’ = b2 – a21 * b1’‌‌‌.(4) ‌‌‌.(5) ‌‌‌.(6)a32’ = a32 – a31 * a12’ a33’ = a33 – a31 * a13’ b3’ = b3 – a31’ * b1’‌‌‌.(7) ‌‌‌.(8) ‌‌‌..(9)1 [0 0a11 gets cancelled‌..and from given equation‌‌‌‌ (1) ‌‌‌‌(2) ‌‌‌‌.(3)Make row 2 as following Instruction R2 = R2/a22+Y=*a12’= a12/a11 a13’=a13/a11 b1’=b1/a11Make row 2 and row 3 as following Instruction R2 = R2 – a21* R1 R3 = R3-a31 *R1 đ?‘‹ 1 đ?‘Ž12′ đ?‘Ž13′ đ?‘?1′ [0 đ?‘Ž22′ đ?‘Ž23′] * [đ?‘Œ ] = [đ?‘?2′] đ?‘? 0 đ?‘Ž32′ đ?‘Ž33′ đ?‘?3′From the above solved Matrix By the Backward Substitution we will get Here Y=b2’’ ‌‌‌.(a) X+a12’Y=b1’ ‌‌‌(b) And from equation (a) Y=b2’’ From eq(5) Y=* + From equation (3),(4) Y=* + From equation (1),(2) Y=*đ?‘Ž12 đ?‘Ž13 đ?‘‹ đ?‘?1 đ?‘Ž22 đ?‘Ž23] * [đ?‘Œ ] = [đ?‘?2] đ?‘Ž32 đ?‘Ž33 đ?‘? đ?‘?3+đ?‘‹ đ?‘Ž12′ đ?‘Ž13′ đ?‘?1′ 1 đ?‘Ž23′′] * [đ?‘Œ ] = [đ?‘?2′′] đ?‘? đ?‘Ž32′ đ?‘Ž33′ đ?‘?3′a23’’ = a23’/a22’ b2’’ =b2’/a22’‌‌‌..(10) ‌‌‌..(11)Make row 3 as following Instruction 78 IJSTRŠ2017 www.ijstr.orgINTERNATIONAL JOURNAL OF SCIENTIFIC & TECHNOLOGY RESEARCH VOLUME 6, ISSUE 03, MARCH 2017R3 = R3 – a32’ * R2 đ?‘‹ 1 đ?‘Ž12′ đ?‘Ž13′ đ?‘?1′ [0 1 đ?‘Ž23′′] * [đ?‘Œ ] = [đ?‘?2′′] đ?‘? 0 0 đ?‘Ž33′′ đ?‘?3′′*(Z=* Z= *[‌‌..(b)*+‌..fromeq(7,8,9,10,11)*()+ *((()) [(( ))+ [ ()()]) ] )Z= *()+ *(([))(())]] *] [+] *[+] [] [] []]+]+ ++] []] [] [] []+]+))+ [From equation (b) Y+a23’’Z=b2’’))] (())(())))+ [Y=[(b2’’)-(a23’’*Z)]] (())]Y= *+-*+from eq(10,11)‌..From eq(1,2,3) ((()*(())+ *(())+ [Z= ()*()+ *((*] (())(())(())))+ [[]([)*(+)+ *(((Y=[((Z=+Y=* ())+ *(()]as well as a11 gets cancelled )*(((Y=*+ gets cancelled(+Y=*))))+ [((())(())(())](Y=[ *))‌..from eq(4,5,6) ))))) (((Y=[]( ((())]))+ [)) (((())) [(()) ((( (] ‌..from eq(1,2,3)))) (()])) ))])]+ will get cancelled‌ 79IJSTRŠ2017 www.ijstr.org+]If r= [(a11*b3) - (a31*b1)]; s= [(a11*b2) - (a21*b1)]; t= [(a11.a22) - (a12*a21)]; u= [(a11*a33) - (a13*a31)]; v= [(a11*a23) - (a13*a21)]; w=[(a11*a32) - (a12*a31)]; Z=*(())+ *((((]‌‌. From eq (1,2,3,4,5,6) *((] [Z= [ *[‌‌.from eq(14)))+ (*))đ?‘Ž11 đ?‘Ž22 − đ?‘Ž21 đ?‘Ž12 gets cancelled‌ Z= [ ] [ * [[ ] [ *‌‌.fromeq(12)&(13)([] (())+ [*‌‌‌‌..(14)Z=**()+ *(([‌‌..(a)Z=[))+ [[‌‌‌‌(12) ‌‌‌‌(13)Z = b3’’’ Y+a23’’Z=b2’’ From equation (a) We get Z = b3’’’ Z=* +=))+ *((Z=Make row 3 as following Instruction R3 = R3/a33’’ đ?‘‹ 1 đ?‘Ž12′ đ?‘Ž13′ đ?‘?1′ [0 1 đ?‘Ž23′′] * [đ?‘Œ ] = [ đ?‘?2′′ ] đ?‘? 0 0 1 đ?‘?3′′′ b3’’’ = b3’’/a33’’ From the above Matrix, By the Backward Substitution we getZ))((*((a33’’ = a33’ - a32’ * a23’’ b3’’ = b3’ – a32’ * b2’’+ISSN 2277-8616+]INTERNATIONAL JOURNAL OF SCIENTIFIC & TECHNOLOGY RESEARCH VOLUME 6, ISSUE 03, MARCH 2017() [((Y=[)) ((( () (()) ))(Y=*)])ISSN 2277-8616And finally ]X=3 Hence we can conclude+X=3 Y=-1 Z=-2s= [(a11*b2) - (a21*b1)]; t= [(a11.a22) - (a12*a21)]; v= [(a11*a23) - (a13*a21)];B. New Formula Method x-3y+z=4 2x-8y+8z=-2 -6x+3y-15z=9Y=* + And from given equations we get X=* + And here Simultaneously we can derive the formulas for the four unknowns in the same way above derived. As well as we can also derive the formulas for the Simultaneous equations with the number of derivatives.Compare it with a11X+a12Y+a13Z=b1; a21X+a22Y+a23Z=b2; a31X+a32Y+a33Z=b3;4. COMPARISIONThen here for three unknowns Substitute the values in the given formulae Hence we will getA. Gauss Elimination Method x-3y+z=4 2x-8y+8z=-2 -6x+3y-15z=9r= [(a11*b3) - (a31*b1)]; r= 33Convert into AX=B Matrix form Make the Matrix A as Upper Triangular Matrix 1 −3 1 đ?‘‹ 4 [ 2 −8 8 ] * [đ?‘Œ ] = [−2] 9 −6 3 −15 đ?‘?t= [(a11.a22) - (a12*a21)]; t= -2Make row 2 and row 3 as following Instruction R2 = R2 – 2* R1 R3 = R3-(-6) *R1 1 [0 0−3 −2 −151 đ?‘‹ 4 6 ] * [đ?‘Œ ] = [−10] 33 −9 đ?‘?s= [(a11*b2) - (a21*b1)]; s= -10u= [(a11*a33) - (a13*a31)]; u= -9 v= [(a11*a23) - (a13*a21)]; v=6 w=[(a11*a32) - (a12*a31)]; w=-15Make row 2as following Instruction R2 = R2/ (-2)Z=*1 [0 0Z= -2−3 1 −151 đ?‘‹ 4 −3] * [đ?‘Œ ] = [ 5 ] 33 −9 đ?‘?Make row 3 as following Instruction R3 = R3 – (-15) * R2 1 [0 0−3 1 01 đ?‘‹ 4 −3 ] * [đ?‘Œ ] = [ 5 ] 108 −54 đ?‘?And then by Backward Substitution Method We will get -54*Z=108 Z=-2+=*Y=* +=* Y= -1 X=* X=3[] [ []] [[+= *]]+++Hence X=3, Y= -1, Z= -2 Hence here is the solution by the formulae methodY-3*Z=5 Y=-1 80 IJSTRŠ2017 www.ijstr.orgINTERNATIONAL JOURNAL OF SCIENTIFIC & TECHNOLOGY RESEARCH VOLUME 6, ISSUE 03, MARCH 2017ISSN 2277-86165. CONCLUSION: Here we can conclude that there is no confusion in solving the simultaneous equation by the Formulae Method. As well as it is easier and takes less time than the other methods like Gauss Elimination Method, Gauss Seidal Method, etc. And in the Engineering Calculators like CASIO fx-991ES PLUS there is no solution for the simultaneous equation with four unknowns so we can use these formulas for solving the Simultaneous equations easily as well as fast.6. REFERENCES: [1]Steven C. Chapra, Raymond P. Canale, Numerical Method for Engineers. 4/e, Tata McGraw Hill Editions, 2002, ISBN 0-07-047430[2]Dr. B. S. Garewal, Numerical Method in Engineering and Science, 7/e, Khanna Publishers, ISBN81-74009-205-6[3]Steven c. Chapra, Applied Methods in MATLAB for Engineers and Scientist, 2/e, Tata McGrawHill Publishing Co.Ltd, 2008, ISBN007-064853-0[4]M. K. Jain, S R K Iyengar, R K Jain, Numerical Method for Scientific and Engineering Computations, 5/e New Age International Publisher ISBN 13 978-81-224-2001-2008[5]Gary D. Knott, "Gaussian Elimination and LUDecomposition", www.civilized.com, Feb 28, 2012[6]Joseph F. Grcar, ―Mathematicians of Gaussian Elimination‖, Notices of the AMS, June 2011[7]Nondeterministic Procedure of Solving Simultaneous Equations, N. Shobha Rani, Research scholar, Maharaja Research Foundation, MIT, Mysore, International Journal of Engineering and Science Issn: 2278-4721, Vol. 2, Issue 3 (February 2013)81 IJSTR©2017 www.ijstr.org

Trabalho - Molas

Aug 11, 2017
Search
Similar documents
Related Search
We Need Your Support
Thank you for visiting our website and your interest in our free products and services. We are nonprofit website to share and download documents. To the running of this website, we need your help to support us.

Thanks to everyone for your continued support.

No, Thanks